Nuclear Heme Oxidase-1 Inhibits Endoplasmic Reticulum Stress-Mediated Apoptosis after Spinal Cord Injury. (3rd August 2020) - Bi, Yunlong; Chen, Xi; Cao, Yang; Yu, Deshui; Zhao, Jia'ai; Jing, Yu; Lv, Gang
Abstract : The treatment goal for spinal cord injury (SCI) is to repair neurites and suppress cellular apoptosis. This study is to investigate the effects of nuclear heme oxidase-1 (HO-1) on the acute spinal cord injury and the related mechanisms. The rat model of the SCI was established. On day 7, before model establishment, the adenovirus vector carrying nuclear HO-1 (Ad-GFP-HO-1C Δ 23) was injected into the animals into the tenth thoracic spine (T10) segment by the intrathecal injection. Starting from after the model establishment to day 28, the recovery of motor function was assessed by the Basso-Beattie-Bresnahan (BBB) scoring method. Immunofluorescence was performed to detect the expression patterns of nuclear and cytoplasmic proteins. HE and Nissl staining methods were used to evaluate the structural damage and the number of surviving neurons near the injured area. The TUNEL method was conducted to evaluate the apoptotic degree. Protein expression levels were detected with the Western blot analysis. The BBB assay scores in the nuclear HO-1 group were significantly higher than the blank and adenovirus control groups. Moreover, compared to the blank and adenovirus control groups, the neuronal apoptosis in the nuclear HO-1 group was significantly alleviated. Furthermore, the expression levels of the endoplasmic reticulum stress-related proteins, i.e., CHOP, GRP78, and caspase-12, were significantly decreased in the nuclear HO-1 group. Nuclear HO-1 significantly improves the SCI, promotes the functional recovery, inhibits the endoplasmic reticulum stress, and alleviates the apoptotic process after SCI.